Evaluasi Pembelajaran IPA dengan Menggunakan Instrumen Non Tes pada Siswa Kelas IV Sekolah Dasar - Ina Magdalena; Dian Andriani Suherdi; Indah Aprianti; Wahyuni Desti Utami (Jurnal Halaqah, 2021)
This study aims to see the description of fourth-grade elementary school students in science learning using non-test evaluation instruments. The results of this study explain that fourth-grade elementary school students do not understand how to learn science by using non-test evaluation. It is necessary for students to encourage students to be interested in learning and exploring information in science learning activities, which is one of the subjects at the basic education level by focusing on studies on nature and its surroundings and the process of helping students develop abilities in science learning. This research was conducted at SDN Periuk 6. Furthermore, class teachers and principals at SDN Periuk 6 were also used as information to obtain as much data and information as possible to see how students can think critically for practice around the school in learning natural knowledge.